Automobile Origin and Maintenance - Sattorov Fozil Jumayevich (Genius Journals, 2023)
The first car was created on the rock and when, what kind of vehicle was it before the cars? When were the engines that were the source of action created? What are the types of engines? To find answers to questions about what automobiles are being created today, it is important to look at the history of the car. The article contains similar problematic questions, relying on existing sources.
Keywords: motion vehicle; vehicle